2008
DOI: 10.1037/0097-7403.34.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The relative influence of place and direction in the Morris water task.

Abstract: Previous work from our laboratory has demonstrated that rats display a preference for directional responding over true place navigation in the Morris water task. The present study evaluated the range of situations in which this preference is observed and attempted to identify methods that favor navigation to the precise location of the escape platform in the room. A preference for directional responding over place navigation was observed in a wide range of procedures that included providing extensive training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
109
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(123 citation statements)
references
References 41 publications
13
109
1
Order By: Relevance
“…The data from Experiment 2 are also consistent with Blodgett et al 's ( 1949) In contrast to earlier findings by Hamilton et al (2008), making the pool wall transparent did not encourage place learning when the maze was translated. The absence of a place strategy in the water T-maze may be due to the dominance of response and direction solutions in an apparatus with confined movement trajectories.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The data from Experiment 2 are also consistent with Blodgett et al 's ( 1949) In contrast to earlier findings by Hamilton et al (2008), making the pool wall transparent did not encourage place learning when the maze was translated. The absence of a place strategy in the water T-maze may be due to the dominance of response and direction solutions in an apparatus with confined movement trajectories.…”
Section: Discussioncontrasting
confidence: 54%
“…In a pilot experiment, it was shown that acquisition of the translation place problem was difficult in the water maze. However, Hamilton et al (2008) demonstrated a preference for place navigation over directional responding using the open maze configuration when the pool wall was removed as a prominent cue. Consequently, in Experiment 2 acqui ition of place learning was assessed in a new water T -maze with transparent Plexiglas walls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings, however, question this assumption. Specifically, it was discovered that adult rats do not search for the platform at its absolute spatial location when the pool is repositioned in the testing room during a posttraining probe trial (Hamilton et al, 2008;Hamilton, Akers, Weisend, & Sutherland, 2007). Instead, they continue to swim in the same direction that the platform was located during training, resulting in a search for the platform at a spatial location that was never trained.…”
mentioning
confidence: 99%
“…To disambiguate directional responding and place navigation in the Morris water task, we developed two variants of the task that specifically require either direction or place responses (Hamilton et al, 2008). In both variants of the task, the pool is repositioned in the distal cue environment for every trial.…”
mentioning
confidence: 99%